An Analysis of Independence in Audit Process - Ana María Pina-Martínez García (Revista Galega de Economía, 1970)
The goodness of the audit process depends on how it happen in auditor's mind who does it, how it happen its phases, its content and completion. Auditor independence becomes one of the fundamental pillars of the exercise of audit activity. The aim of this paper is to analyze how this concept has been developed, both at international and national lines and anticipate future developments in more or less close. This analyzes the main legal texts that have shaped the independence of the auditor, whose regulation has pivoted on three issues: the services cannot provide the auditor, perceived fees and duration of the audit contract. We conclude with some reflections on the importance of auditor independence and quality control system.